ANALISIS PENDAPATAN DAN KESEJAHTERAAN PRODUSEN JAMUR TIRAM DI KOTA METRO - Silvya Dara Mitha; Dwi Haryono; Novi Rosanti (Lampung University, 2015)
The purposes of this research are to: (1) determine income oyster mushroom producer in Metro City, (2) determine welfare level of oyster mushroom producer in Metro City. This experiment was conducted in Metro City that was chosen by purposive in December 2013 until May 2014. It was considered that the Metro City has high enough in producing the oyster mushroom. This study takes 42 producers. This study used a census method with qualitative and quantitative analysis. Analysis of the data used descriptive qualitative analysis with tabulation method and descriptive quantitative analysis. The results showed that: (1) The average income of oyster mushroom in Metro City was in high income, consist of farming income of their own activities (on farm), from outside of their own activities (off farm) and from outside of farming activities (non farm). The biggest income of oyster mushroom in Metro City is sourced from income of oyster mushroom farming, (2) Most of oyster mushroom farmer in Metro City was in enough and in suitable live based on Sajogjo’s criteria (1997), and also included to welfare category based on the criteria of BPS (2007). Key words: income, mushroom, producer, welfare